2008
DOI: 10.1007/s11604-007-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Serial diffusion tensor imaging to characterize radiation-induced changes in normal-appearing white matter following radiotherapy in patients with adult low-grade gliomas

Abstract: Radiation-induced changes in NAWM can be detected at 3 months after RT, with changes in FA, CL, and CS (but not CP or MD) values seen at a threshold dose of 45-50 Gy. A partial recovery was evident by 14 months to regions that received doses of 50-55 Gy and >55 Gy, thus providing an objective measure of radiation effect on NAWM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 33 publications
(37 reference statements)
10
43
0
Order By: Relevance
“…Earlier it has been reported that the CS truly reflect isotropic behavior of water molecule while MD does not [45]. Further, it has been shown that the increased BBB permeability results in increase CS value [45]. Strong direct correlation between MMP-9 and CS in the current study also suggests that the CS is more sensitive than MD in measuring the increased water concentration due to the MMP-9 induced BBB damage as well as ECM degradation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Earlier it has been reported that the CS truly reflect isotropic behavior of water molecule while MD does not [45]. Further, it has been shown that the increased BBB permeability results in increase CS value [45]. Strong direct correlation between MMP-9 and CS in the current study also suggests that the CS is more sensitive than MD in measuring the increased water concentration due to the MMP-9 induced BBB damage as well as ECM degradation.…”
Section: Discussionsupporting
confidence: 61%
“…In the current study, increased MD and CS values in cellular fraction of BT compared to normal brain parenchyma suggests increased interstitial fluid due to the degradation of the ECM by high MMP-9 expression in cellular fraction of the BT. Earlier it has been reported that the CS truly reflect isotropic behavior of water molecule while MD does not [45]. Further, it has been shown that the increased BBB permeability results in increase CS value [45].…”
Section: Discussionmentioning
confidence: 96%
“…A possible cause of the discrepancy is the effect of concomitant chemotherapy (which our patients did not receive) in those studies because chemotherapy alone can alter normal white matter structures (26). This postulation is supported by a longitudinal study on patients not receiving chemotherapy (27), which showed a recovery or no further progression at 8 or 14 months after therapy and no change when the average dose was less than 45 Gy. Other possible causes of the discrepancy could be whole brain irradiation (15) as opposed to focal irradiation by proton therapy, higher dose to the target volume (range, 50-81 Gy) (9) than that in the present study (54 CGE), and differences in adult and pediatric patients.…”
Section: Comparison To Previous Dti Studies Of Photon Therapymentioning
confidence: 74%
“…Early works have demonstrated the capabilities of DTI for 3D tracking of axonal projections (8,18). Recent studies have found DTI a potential biomarker of WM damage (15)(16)(17)19). In 2004, Huisman et al (17) reported that changes in the WM detected by DTI could be correlated with diffuse axonal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Chapman et al (19) reported a potential correlation between early diffusion changes and radiation-induced late delayed neurocognitive decline and suggested DTI as a potentially useful biomarker for predicting late delayed cognitive decline. Although radiation-induced WM damage has been investiagted in conventional fractionated radiation therapy (15)(16)(17)19), few studies have been carried out to investigate radiation-induced changes in WM following stereotactic radiosurgery (SRS).…”
Section: Introductionmentioning
confidence: 99%